ENVIRONMENTAL PROCEDURE LAW: THE AMAZON AND LEGAL LIABILITY IN ENVIRONMENTAL PROTECTION (REMUNOM, 2025)
The present article focuses on Environmental Law and the legal instruments that enable the defense and preservation of the environment within the Brazilian legal system. It addresses highly important procedural mechanisms, such as the environmental popular action, the collective environmental writ of mandamus, and the environmental writ of injunction, which allow for the protection of various rights. The objective is to understand the aforementioned legal instruments that guarantee environmental protection and encourage active societal participation in the implementation of environmental policies. This study utilizes fundamental concepts, doctrinal interpretations, and case law to discuss the efficiency and challenges arising from the implementation of such norms within the Brazilian legal framework.